The Influences of Aminophylline and Indomethacin in Glycerol-Induced Acute Renal Failure in Rats - Mahdi, Estabraq M. (AL-Kindy College Medical Journal, 2010)
Background: Adenosine mediates homodynamic changes and resulted in the production of acute renal failure (ARF) in female Albino-Wister rats, therefore, adenosine level increases highly in ARF. Objective: This experiment was designed to investigate the effect of the adenosine antagonist aminophylline and the adenosine agonist indomethacin on glycerol-induced ARF. Method: Glycerol induced ARF was produced by a single dose (10ml/kg, 50%v/v with distilled water i.m) in rats, which were restricted to drinking water. Aminophylline was used in our study in a dose of 25mg/kg, i.p) while the dose of indomethacin was 10mg/kg, i.p), assessment of renal function was done by measuring blood urea nitrogen (BUN), serum creatinine (Scr), and creatinine clearance (Ccr) Results: Aminophylline exert its protective effect against glycerol induced-ARF by lowering the elevation in concentrations of BUN, Scr, and mortality rate with a markedly attenuation of the sever impairment Ccr. On the other hand, indomethacin potentiates glycerol induced-ARF by significantly increase the elevation in concentrations of BUN, Scr and mortality rate with severely suppressed the decrement in Ccr. Conclusion: Aminophylline has ameliorating effect on glycerol induced ARF while the prostaglandin inhibitor indomethacin has reversed effect